DESKRIPSI KEGIATAN EKONOMI MASYARAKAT SEKITAR DESTINASI WISATA MANGROVE POLARIA TANJUNG PAGAR DI DESA MENDALOK KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Mustika Mustika; Budiman Tampubolon; Nur Meily Adlika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The Covid-19 pandemic has paralyzed tourism and decreased tourist visits, one of which has been affected is the Polaria Tanjung Pagar mangrove tourist destination in Mendalok Village, Sungai Kunyit District, Mempawah Regency, while traders depend on tourist visits, the more tourists visiting the more There are also many income opportunities for traders. This study aims to determine the condition of the Tanjung Pagar Polaria Mangrove tourist destination during Covid-19 and to determine the economic activities of the community around the Tanjung Pagar Mangrove tourist destination during Covid-19. The type of study in this research is a qualitative research. The population in this study was the community around the Tanjung Pagar Mangrove Polaria tourist destination, totaling 11 people using snowball sampling. The data used in this study were observed, interviewed and recorded. Analyzing data using Miles and Humberman analysis. The results of this study indicate that to see the condition of the Polaria Tanjung Pagar mangrove tourist destination seen from accessibility, attractions, and amenities. Meanwhile, to see the economic activities of the community around the Polaria Tanjung Pagar mangrove tourist destination, it can be seen from the changes in the livelihoods of the surrounding community. Prior to the existence of this destination, the local community worked as fishermen, but since the existence of the Polaria Tanjung Pagar mangrove tourist destination, the surrounding community can open up opportunities for their own work by trading snacks so that visitors do not have to go out to buy food.